Polarization rotators fabricated by thermally-switched liquid crystal alignments based on rubbed poly(N-vinyl carbazole) films - Chen, Yuan-Di; Cheng, Ko-Ting; Liu, Cheng-Kai; Fuh, Andy Ying-Guey (Optics express, 2011)
This paper demonstrates the thermally-switched liquid crystal (LC) alignments based on a rubbed poly(N-vinyl carbazole) (PVK) film, and their application for polarization rotators. The mechanically rubbed PVK layer can induce a planar alignment of LCs with their director axis perpendicular to the direction of rubbing. This direction can be switched toward the rubbing direction by thermal treatment. Experimentally, the angle of re-orientation of the director axis increases with the temperature in a specific range of temperatures. In this study, the optical properties of linear and concentric polarization rotators, fabricated using a rubbed PVK film with thermal treatment, are examined.